2016
DOI: 10.3389/fninf.2016.00013
|View full text |Cite|
|
Sign up to set email alerts
|

ToolConnect: A Functional Connectivity Toolbox for In vitro Networks

Abstract: Nowadays, the use of in vitro reduced models of neuronal networks to investigate the interplay between structural-functional connectivity and the emerging collective dynamics is a widely accepted approach. In this respect, a relevant advance for this kind of studies has been given by the recent introduction of high-density large-scale Micro-Electrode Arrays (MEAs) which have favored the mapping of functional connections and the recordings of the neuronal electrical activity. Although, several toolboxes have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
(52 reference statements)
0
26
0
Order By: Relevance
“…It is interesting to observe how the accuracy data for d =1/9, i.e. prior to using the reconstruction algorithm based on the discriminator threshold d ( Figure 4I, d=1/9), showed performances already higher than 75% for a network of 10 neurons, and even higher for larger sizes, thus exceeding the ones obtained before standard thresholding in published connectivity methods [62]. The complete reconstruction algorithm led to a computational accuracy close to 100% for all network sizes due to the further statistical pruning of false positive connections ( Figure 4I, d =1).…”
Section: Numerical Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…It is interesting to observe how the accuracy data for d =1/9, i.e. prior to using the reconstruction algorithm based on the discriminator threshold d ( Figure 4I, d=1/9), showed performances already higher than 75% for a network of 10 neurons, and even higher for larger sizes, thus exceeding the ones obtained before standard thresholding in published connectivity methods [62]. The complete reconstruction algorithm led to a computational accuracy close to 100% for all network sizes due to the further statistical pruning of false positive connections ( Figure 4I, d =1).…”
Section: Numerical Resultsmentioning
confidence: 93%
“…In this work, we demonstrated a new model-free based approach to reconstruct effective and functional connections from in vitro neuronal networks recorded on MEAs. Our algorithm offers several fundamental differences resulting in critical advancements compared to the state-of-theart connectivity techniques, including correlation and transfer entropy variants [25,62]. To the best of our knowledge, model-free connectivity inference techniques are not able to reconstruct the effective -causal and direct -connections of a recorded neuronal network because they are either missing the causality of signaling or include confounding apparent connections (common input or common output) and multi-neuron pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, using three bins instead of four will produce different results, especially in terms of information values (see Daw et al (2003) for a review of discretization methods and their impacts on data analyses from a more general perspective). Several more advanced methods have been developed, some of which are implemented in other software packages, to overcome these problems in certain cases (Nemenman et al, 2002; Goldberg et al, 2009; Ince et al, 2009; Magri et al, 2009; Ito et al, 2011; Lindner et al, 2011; Pastore et al, 2016). Furthermore, even with the basic analysis methods presented herein, statistical testing methods exist to reduce the appearance of false-positive information theory results caused by discretization and bias effects (see Significance Testing ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that many of these other packages are focused on a narrower type of analysis. Several software packages have been introduced to calculate transfer entropy (Ito et al, 2011; Lindner et al, 2011; Montalto et al, 2014; Pastore et al, 2016), often with the emphasis on estimating neural connectivity. Also, several software packages have focused on estimating entropy and mutual information using more advanced techniques (e.g., binless and kernel estimation techniques, as well as bias correction) than those presented herein to address problems surrounding continuous data and binning (Goldberg et al, 2009; Ince et al, 2009; Magri et al, 2009; Lindner et al, 2011; Lizier, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation